Half a century Monuments and Historic Buildings Act: 1961-2011 (Bulletin KNOB, 2012)
The Dutch Monuments and Historic Buildings Act dates from 1961. Naturally, the Act was primarily intended to protect old buildings. In the first place the traditional heritage: churches, town gates, town halls and the houses of aristocrats. Soon architecture from a more recent past, the period 1850-1940, was also placed on the historic buildings register. The Act as an administrative instrument for the conservation of historic buildings was a great success. Consequently, the intentions of the legislator were fully complied with, but the Act had social side effects which may have been even more important, for the Monuments and Historic Buildings Act caused a national change of mentality.The importance of heritage has gradually become a matter of course in the Netherlands. For a long time it was common practice, even in public administration, to indicate historic buildings as ‘old junk’. The many editions of the journal Heemschut give a clear picture of the battle that had to be waged for years on end in order to preserve at least some part of the many age-old city and village cores in the Netherlands. Notably the post-war decades were a dramatic period. Modernisation and renovation were the highest priorities among the municipal authorities. The Monuments and Historic Buildings Act formed a turning-point in this battle, though not overnight. The Act initiated a process of awareness that finally resulted in a very broad social basis for preservation of heritage.These past years this development has even accelerated, whereby the still broader definition ‘cultural history’ is used more and more frequently. As the interest in the quality of the built environment was increasing, people were also becoming more aware of the fact that historic buildings and spatial structures highly contribute to the quality of life in town and countryside. Protection was possible by means of the instrument ‘village and urban conservation area’, but the Dutch citizen was also becoming more and more critical and assertive; people acquired an eye for their own living environment as a ‘patrimony’, however modest, and thus the administrative boundaries of the Monuments and Historic Buildings Act were gradually getting in sight. Not every street profile can reasonably be protected. Post-war mass housing with the accompanying urban patterns is ill suited for protection by means of the Monuments and Historic Buildings Act. The appearance of the post-war residential districts is characterized by low-density building, the corresponding public greenery, and much repetition in architecture. The Amsterdam residential district Slotermeer, with 10,000 dwellings, is a typical example. It would not make sense to place all these dwellings on the historic buildings register, but is is just as pointless to preserve just one or a few ‘museum dwellings’. The post-war residential districts form very large sets which should be ‘protected’ in a different way.However, the question is how. At present the aim is to arrange a form of protection in the zoning plan, so by way of the Spatial Planning Act. The main issue is finding a balance between preservation of special modern townscapes and the necessity to modernize notably the frequently small and outdated rented houses. No one knows exactly how this should be done. A requirement is at any rate the willingness to conduct a dialogue. So far, the Dutch housing corporations have not shown any interest in the historical significance of post-war housing. In these circles the term ‘old junk’ is still unconcernedly used.